Pelatihan Strategi Metakognisi Membaca untuk Menguatkan Membaca Pemahaman Siswa Kelas V SDN 192 Pekanbaru - Latif Latif; Hidayatun Nur (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This Community Service Activity was carried out at SDN 192 Pekanbaru with the title Training on Reading Metacognition Strategies to Strengthen Reading Comprehension of Grade V Students of SDN 192 Pekanbaru City. The activity was carried out using qualitative research using observational data collection and interviews. This activity used a contextual approach in the form of training and exercises. The purpose of the training was to improve teachers' and students' knowledge and understanding of reading metacognition strategies in reading comprehension. The teacher training activity was carried out on February 14, 2026 and February 21, 2026, reading metacognition training for grade V students of SDN 192 Pekanbaru. The results of the training: (1) Strengthened understanding of reading metacognition strategies by teachers which include prediction, questioning, clarifying, summarizing, and monitoring or checking strategies; (2) Strengthened students' understanding of reading metacognition strategies applied in the reading comprehension process. Based on final observations and interviews, the training was very helpful in strengthening teachers' understanding of metacognition strategies applied in reading comprehension. For students, the training accompanied by the exercises provided was useful for increasing reading comprehension knowledge and improving student learning outcomes